Determination of Polar Cap Boundary for the Substorm Event of 8 March 2008 - Wang, Chi; Wang, Jiangyan; Lopez, Ramon; Li, Hui; Zhang, Jiaojiao; Tang, Binbin (Frontiers in Physics, 2018)
The polar cap boundary (PCB) is a fundamental indicator of magnetospheric activities especially during a substorm cycle. Taking a period on 8 March 2008 as an example, we investigate the location of PCB and its dynamics during a substorm event. The PCB location is determined from the Piecewise Parabolic Method with a Lagrangian Remap (PPMLR) -Magnetohydrodynamic (MHD) simulation data and Defense Meteorological Satellite Program (DMSP) observations, respectively. Model-observation comparison indicates that the PPMLR-MHD model gives a reliable estimate of PCB location during a complex substorm sequence. We further analyze the evolution of PCB in that period. The polar cap expands under southward interplanetary magnetic field (IMF), since the low-latitude dayside reconnection produces new open magnetic flux. Meanwhile, more solar wind energy enters and stores in the magnetosphere with the decreasing SML (SuperMAG Auroral Lower) index. After the substorm expansion onset, the polar cap contracts for a while due to the explosive increase of nightside reconnection. When the IMF direction turns northward, the polar cap contracts continuously, since the dayside reconnection ceases and no more open magnetic flux are supplied, and the storage energy in the magnetosphere releases with the increasing SML index. The model results are in good accord with the features from observations.